Prognostic and Predictive Significance of Microsatellite Status in Patients with Colorectal Cancer in Stage II and Stage III Disease: Single-Centre Experience - Perović, Jelena; Radić, Jelena; Djuric, Aleksandar; Marjanovic, Marko; Urosevic, Teodora; Radovanović, Bojan; Kožik, Bojana (Archive of Oncology, 2025)
Background: Colorectal cancer (CRC) is one of the leading causes of cancer-related morbidity and mortality worldwide. Microsatellite instability (MSI) is a crucial biomarker with prognostic and predictive value, influencing treatment decisions in CRC. Methods: This retrospective study investigated the impact of the MSI status on clinical outcomes in 184 CRC patients treated at the Oncology Institute of Vojvodina between 2018 and 2023. The MSI status was determined using the immunohistochemical analysis of mismatch repair proteins. Results: Among the cohort, 75% of tumors were microsatellite-stable (MSS), 4.3% exhibited low MSI (MSI-L), and 20.6% displayed high MSI (MSI-H). MSI-H tumors were significantly associated with right-sided CRC, mucinous differentiation, and female gender (p<0.05). The survival analyses revealed that the MSI-H patients with stage II disease had significantly better disease-free survival (DFS) and overall survival (OS) than the MSS counterparts (p=0.024 and p=0.006, respectively). Conversely, the MSI-H status in stage II patients receiving adjuvant therapy was linked to shorter DFS (p=0.000), highlighting the limited benefit from 5-fluorouracil-based regimens. In stage III CRC, the MSI status did not significantly affect DFS or OS. Conclusion: These findings underscore the dual role of MSI as a favorable prognostic marker in early-stage CRC and a predictor of the reduced benefit from adjuvant chemotherapy in stage II disease. This study emphasizes the need for individualized treatment strategies based on the MSI status and supports the potential integration of immunotherapy in the adjuvant setting for MSI-H CRC.